Beyond access gender and transport justice in Davao City, Philippines - Rivera, Roselle Leah K. (International Institute of Social Studies of Erasmus University (ISS), 2021)
Transportation is more than just a technological concern; what is central are people’s aspirations which are also intertwined with a country’s development goals. When transport is grounded on people’s experiences, it becomes more nuanced and responsive to their needs. This in turn has implications on how the idea of transport and development is envisioned and implemented, that is, not primarily considering “First World” technocratic standards but rather one which is contextualized in the user’s realities – their geo-political location, resources, capabilities, and their way of life. Feminist contributions to urban transport studies belong to broader debates on the place of transport in enhancing human capabilities and social rights (Fainstein, 2010; Nussbaum, 2005). Other work in critical urban studies focuses on the relationship between social identities (gender, class, age, race, or a confluence of these), and safety in urban contexts. 'Urban transport' in the ‘development’ debate reveals that while development studies have freed itself from a technocratic model based on notions of efficiency, urban transport studies are only starting to embrace the right-based perspective and a consultative model of planning. This study brings together these emerging perspectives in urban transport studies in an attempt to integrate them under the concept of transport justice – to be treated as part of a broader struggle for environmental justice (Schlosberg, 2013; Schweitzer & Valenzuela, 2004), civil rights (Soja, 2010; Harvey, 2003) and inclusive cities (Roy, 2010). The study’s framework on transport justice, intersecting with gender justice, builds on three concepts: redistribution, recognition, and representation. The research was designed as a multilayer exploration which covers the different levels of interplay between notions of "gender" and "transport" to elucidate the marginalization of the interests of low-income users, the majority being women traders and workers. Placed in a context of “development”, i.e., intra-city land transport in Davao City, Mindanao, The Philippines, “transport justice” is applied as a normative framework to bring to light three clusters of gender issues. Transport justice, as expounded in this study, highlights (1) the concrete reality of unequal distribution of transport resources, such as safe modes of transportation, public infrastructure, as well as real options for transport which considers factors such as the users’ financial and cultural context; (2) the inequality of representation, if not invisibility, of certain transport users, in the discourse of transportation, which is often tied to the other forms of discrimination that these groups face; and (3) the cultural and structural barriers to recognize the needs of these groups and therefore the importance to engage these groups. Transport justice, at its core, is about inclusivity in development. Transport justice seeks to integrate the various experiences of users so that transport modes, infrastructure and systems are responsive to their needs at the personal level and to addressing the gaps in transport planning and implementation at the macro level. Recognizing methodological pluralism as an important value in interdisciplinary research, the study uses a combination of methods, each of which has a distinctive role. The survey method was used to capture and quantify similarities and differences among 360 male and female transport users from 12 different workplaces in 3 districts of the city, comprising mostly women traders and workers. Focus-group discussions with transport users, field observations and one-to-one in-depth interviews with a subsample of 8 female users were conducted to gain deeper insights on meanings of “safety” and “security” from the perspectives of the users. Textual analyses were used to look into issues of misrepresentation as well as invisibility that are crucial in a transport justice frame. In light of the view of social policy on safety and security of the body, a close review of road safety data was done through looking into the standards of assessment of the causes cited in various texts. The findings suggest that inequality of access shapes the choice and agency of transport users, which, in turn, contribute to the shaping of intra-city transport systems. A relevant set of questions that has emerged from the findings scrutinize who is harmed by crashes, how conflicts between users of motorized and non-motorized transport are socially distributed, and what are the main mechanisms and consequences from the perspective of transport justice. The questions raised significant discourses on (1) differentiated access to safe transport for men and women; b) how thinking on gender underpins the perceptions, definition of transport needs and infrastructure planning, especially how the interplay between dominant notions of "gender" and "transport" can marginalize the interests of low income users, by way of planning of transport infrastructure, facilities and services; c) gender dynamics within processes of participation of citizens’ groups in policy-making. There are no official data in the transport policy documents of Davao City on the type of people harmed by conflicts of user roles. Police records of crashes were not woven in planning decisions of the short, medium and long-range transport documents studied. Nevertheless, information culled from the medical records and emergency logbooks of one centrally located hospital may instigate more systematic research in the future to stress the urgent need of transport safety in the lives of people in the city. The concept of transport justice in feminist research agendas helps carry 'gender' as an analytical concept and a set of policy concerns to the center stage. Beyond the level of resource allocation to achieve gender parity of access, transport justice also helps to address different levels of representation and participation in transport planning to build inclusive cities.